2020
DOI: 10.1021/acsaem.0c00485
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Gel Polymer Electrolyte with Excellent Cycling and Rate Performance for Enhanced Lithium Storage

Abstract: High-energy rechargeable Li-metal batteries require safer and more reliable electrolyte systems because of the dendrite growth caused by the organic liquid electrolytes. Polymer electrolytes with both high electrochemical and mechanical properties are expected, although they are challenging to prepare. Herein, a novel gel polymer electrolyte (GPE) based on poly(vinylidene fluoride) (PVDF) has been fabricated by introducing laponite nanoplates via a facile solution-casting method. The composite GPE shows a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…However, only a weakened peak at about 2θ = 20.3° can be found for all the electrolyte membranes, which may be due to the substantial reduction on polymer crystallinity caused by the addition of lithium salt . Among them, with the help of laponite clay, the PVDF/(PEO+PVDF)-L SCEs exhibit the lowest crystallinity with the characteristic peak as the weakest and widest one . Moreover, none of the diffraction peaks representing laponite clay appear in the XRD curve of PVDF/(PEO+PVDF)-L SCEs, suggesting the uniform dispersion of clay nanosheets inside the polymer matrix.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, only a weakened peak at about 2θ = 20.3° can be found for all the electrolyte membranes, which may be due to the substantial reduction on polymer crystallinity caused by the addition of lithium salt . Among them, with the help of laponite clay, the PVDF/(PEO+PVDF)-L SCEs exhibit the lowest crystallinity with the characteristic peak as the weakest and widest one . Moreover, none of the diffraction peaks representing laponite clay appear in the XRD curve of PVDF/(PEO+PVDF)-L SCEs, suggesting the uniform dispersion of clay nanosheets inside the polymer matrix.…”
Section: Resultsmentioning
confidence: 91%
“…36 Among them, with the help of laponite clay, the PVDF/(PEO +PVDF)-L SCEs exhibit the lowest crystallinity with the characteristic peak as the weakest and widest one. 37 Moreover, none of the diffraction peaks representing laponite clay appear in the XRD curve of PVDF/(PEO+PVDF)-L SCEs, suggesting the uniform dispersion of clay nanosheets inside the polymer matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Simultaneously, the modified γ-LAO can be evenly dispersed in the matrix, which provides more channels on the interface of the PHOP matrix and LAO. For comparison, the ionic conductivity, melting peak temperature, discharge cycling stability, and C-rate capability of the PHOP-LAO GPE and PVDF matrix GPEs reported in the previous studies are shown in Table . PHOP-LAO has higher ionic conductivity (4.83 mS cm –1 ) than the other PVDF matrix GPEs indicating that the PHOP-LAO GPE prepared in our present study has a favorable effect in LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…Lithium metal, which possesses the extraordinarily high theoretical capacity (3860 mAh g –1 ) and relatively low redox potential (−3.04 V vs standard hydrogen electrode), has been regarded as an attractive anode for rechargeable batteries. Based on the above-mentioned attraction, Li metal plays a vital role in fulfilling the ever-increasing demands for lithium-ion batteries (LIBs) applied in electric vehicles (EVs), hybrid electric vehicles (HEVs), and portable electronic devices. , Nevertheless, the intrinsic high reactivity of Li is thermodynamically unstable with conventional liquid electrolytes. This fact leads to the formation of lithium dendrites and dead lithium during charging–discharging processes, consequently resulting in the deteriorated Coulombic efficiency (CE), short circuit, and even combustion of the batteries. Employments of gel polymer electrolytes (GPEs) to replace the liquid electrolytes have been made to cope with the inherent problems of Li metal batteries. GPEs have been prepared with gelling polymer–salt systems with liquid plasticizer and/or solvents. The interaction between the liquid electrolyte and the polymer matrix could be chemical bonding or physical interaction. Generally, the liquid components contribute to the electrochemical properties of GPEs, and the polymeric matrix is related to the safety and mechanical properties of GPEs. , Recent progresses of GPEs have been toward introduction of smart features, such as self-protection, thermotolerance, and self-healing, to GPEs …”
Section: Introductionmentioning
confidence: 99%